India - Mumbai Urban Transport Project : Guidance Note on Urban Resettlement - Giovannetti, Frédéric (World Bank, 2012)
The purpose of this guidance note is to bridge precisely identify how to implement World Bank resettlement policies in the context of infrastructure projects affecting South Asian largest cities, with a focus on the impacts on poor areas and slums. The guidance note is intended as a tool to help decision makers in Government agencies and in the Bank, particularly in respect of the main aspects: 1) methods to assess and evaluate resettlement issues, 2) development of appropriate packages, considering the legal and political context, 3) establishment of efficient implementation and management mechanisms, in terms of systems and in terms of resources and teams, 4) closure and post-resettlement aspects, with a perspective on precluding hardship on affected people as well as claims and grievances. Special attention is given to the difficult issue of income restoration, including for business owners, as well as the longer term issue of the sustainability of new communities of resettled people. The overarching aim of this exercise is to approach these issues in a way which will foster sustainable urban development; in short, to identify win-win outcomes including facilitation of the transition from the informal to the formal sector of the urban economy.